EVALUASI TEOLOGIS TERHADAP RASISME - Made Nopen Supriadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2017)
The term race has been applied to humans, so humans began to group themselves among their races, then the emergence of the superiority of the human race against other races is often called racism. Is this really the case of humans, does the Bible agree that humans are divided into racial concepts, how does the Bible state the creation of man against the facts of the human race. Therefore, through this paper will write how God views the reality of the human race.